MAXIMUM POWER POINT TRACKING ALGORITHM TO PHOTO-VOLTAIC SYSTEM UNDER DYNAMIC CONDITIONS - Pallavi T. Sawant; C. L. Bhattar (International Journal of Innovations in Engineering Research and Technology, 2021)
The rapid increasing energy demand of world has put pressure on conventional fossil fuels which are declining because of their limited stock. To fulfill worlds ever rising power demand, solar energy is becoming growing up and promising technology due to its cleanliness and abundant source of energy. But its performance is greatly affected due to dynamic weather situations which lead to power reduction. So to utilize maximum power from photo-voltaic (PV) system, maximum power point tracking is necessary. This paper deals with MATLAB simulation of photo-voltaic system with boost converter. The characteristics of solar system for different critical factors have been discussed. The MATLAB simulation of perturb and observe (PO) method has done and its effectiveness is verified for various factors.